Evaluation of an analytical model for adhesively bonded repair in composite plates. - Guilherme Garcia Momm (2004)
The increasing appliacations of composites in aeronautical structures and the resulting need for joining and repairing them impose the necessity of accurate and practical design tools. This works aims at evaluating the applicability of a one-dimensional analytical model for adhesively bonded scarf repair in composites plain plates under in-plane tension. The elastic part of this model is thoroughly described and improvements in its mathematical formulation are included. Then, the algorithm is implemented using MATLAB. This computational code is validated by means of a comparison of its output to the results of a simple example solved by hand. The code outcome concerning the analysis of adhesive shear strain distribution seems reasonable, except for negative values obtained for certain configurations. Next, the same problem is approximated by a set of different two-dimension finite element models, computed using the MSC.NASTRAN solver. This set comprises stepped-lap joint models, with different degrees of mesh refinement, and a scarf joint model. Based on their results, the difficulty in meshing such joints is highlighted, the advantages of the utilization of locally refined meshes are emphasized, and singularities are identified. Finally, the comparison of the analytical to the numerical results leads to the conclusion that the analytical model is applicable only to qualitative studies of joints between (or repairs in) laminates with a relatively high number of plies.